Analisis Kesetaraan Gender dalam Bidang Ketenagakerjaan Di Indonesia - Yeni Nuraeni; Ivan Lilin Suryono (Nakhoda: Jurnal Ilmu Pemerintahan, 2021)
The issue of gender equality in the field of employment is still widely discussed in various countries, including Indonesia. Although various protections have been sought through international and national legal products, the cultural background in a country will still play an important role in efforts to make gender equality in employment. The research aim is to analyze the level of gender equality on employment in Indonesia and the challenges in achieving gender equality in employment. This study uses qualitative analysis with primary data collection through Focus Group Discussion (FGD). The results of the study show that gender inequality still occurs in Indonesia, but over time the inequality is getting smaller, meaning that the opportunities for women and men are getting equal. However, to improve gender equality, there are still some institutional and sociocultural obstacles, such as the lack of agreement between women workers and employers on gender equality in the workplace, gender equality regulations are still not optimally enforced, workers' awareness of their rights is still low, and bargaining position of women workers. For this reason, the government needs to improve gender equality by increasing law enforcement related to gender equality in employment by involving coordination between the central and local governments in strengthening the labor inspection system. In addition to raising awareness of the gender equality rights of the female workforce and providing social protection for women workers in the informal sector.